Paediatric ovarian tumours and their associated cancer susceptibility syndromes. Issue 1 (24th November 2017) - Goudie, Catherine; Witkowski, Leora; Vairy, Stephanie; McCluggage, W Glenn; Foulkes, William D
Abstract : Non-epithelial ovarian tumours are rare neoplasms that occasionally arise in childhood and adolescence. They can be associated with various cancer susceptibility syndromes. The morphological overlap seen across these tumours and their rarity can make the diagnosis challenging. In the case of an incorrect diagnosis, the underlying genetic susceptibility may be missed. In this review, we outline the genetic background of ovarian non-epithelial tumours arising in children, emphasizing the genes harbouring pathogenic germline variants associated with each tumour type. Specifically, juvenile granulosa cell tumours, Sertoli-Leydig cell tumours, sex cord tumours with annular tubules, Sertoli cell tumours, germ cell tumours and small cell carcinoma of the ovary of hypercalcaemic type are discussed in this review. For each tumour type, we detail the personal and family history features and the presenting characteristics of the ovarian tumour as well as the pathological features and molecular markers that point towards a cancer predisposition syndrome. Throughout, we stress the need for specialised pathological review in difficult cases.